Analisis Kemampuan Pemecahan Masalah Dalam Menyelesaikan Soal Matematika Di SMK - Retno Wulandari; Yulia Haryono; Lita Lovia (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research is motivated by the lack of students' ability to solve problems. The purpose of this research is to find out how the ability to solve problems. The type of research used is descriptive-qualitative with a case study research design. The research subjects were in class XI TPM 1 which consisted of 18 students. The subject chosen for the interview was one student who was selected based on his test results. The research instrument was test results in the form of essays and interviews. The results of the research that has been done show that the most problem-solving abilities are at the re-examining stage.